Stone Matrix Asphalt (SMA) with Construction Waste and Curauá Fiber (Ananas erectifolius) (Research, Society and Development, 2020)
The SMA mixtures are characterized by a high void ratio, which favors binder draindown. In order to avoid this effect, fibers are added to the mixture, which in this case came from Curauá da Amazônia (Ananas erectifolius). The final composition studied resulted in 75% coarse aggregate, 15% fine aggregate, 10% filler, 0.3% of the Curauá fiber residue, and CAP contents equal to 6.50% and 6.88% for the formulations with SMA-Crushed Stone (reference) and SMA-construction and demolition waste (alternative), respectively. The results showed for the Tensile Strength that the composites with CDW reached higher results. The Resilient Modulus values presented small variations for the set of compositions in all loading levels at a temperature of 25°C. However, at a temperature of 40°C, the aforementioned parameter presented decreases in both researched formulations. In general, at all levels examined, higher results were observed for the alternative mixture (SMA-CDW). It is noteworthy the highest results of this parameter when comparing the compositions with the Curauá fiber residue and the formulations mentioned in the literature, with the presence of other types of fibers. Regarding the increase in temperature, there was a decrease in results for both mechanical parameters (TS, DM), but with lower losses for the SMA-RCD composition.